`Save the queen`: female national wheelchair basketball players in gender-segregated and gender-mixed competitive sport - Greve, S.; Süßenbach, J. (German Journal of Exercise and Sport Research, 2022)
In the German National Wheelchair Basketball League, men and women play together. On the national teams, on the other hand, they play separately according to gender. In addition, people without disabilities can also participate in wheelchair basketball. The differences in terms of disability and gender are to be classified and, if possible, eliminated in the competition with a classification system. The intersectional analysis of 12 biographical interviews with current national team players shows a clear reproduction of a traditional gender order. The women report various hierarchical relationships on the playing field that are obviously based on gender. Men play in more important positions and are considered more efficient. Yet these phenomena are mostly taken for granted and hardly questioned. Likewise, certain characteristics are attributed and certain roles are assigned to female players based on their gender. The men interviewed do not see these phenomena or do not reflect on them critically. The difference category of disability also has an influence on the competition setting and the gender discrimination.